Prosociality and morality through the lens of personality psychology. (23rd November 2018) - Smillie, Luke D.; Lawn, Erin C. R.; Zhao, Kun; Perry, Ryan; Laham, Simon M.
Abstract : Prosociality and morality are critical to the functioning and flourishing of society. There is, however, great variation in the degree to which individuals help or hinder one another, or adhere to ethical standards of "rightness." One way to understand this variation is by drawing on theories and models within personality psychology, which may illuminate the basic individual characteristics that drive a wide range of other‐regarding tendencies. In this review, we provide a snapshot of three research strands addressing these themes. The first concerns how personality traits map onto prosocial preferences for fairness and cooperation, as studied using classic social decision‐making tasks called economic games. The second concerns the robust associations between personality traits and indicators of inter‐group prejudice (e.g., authoritarian ideology). The third concerns the emerging concept of moral exceptionality, and the personality traits that may characterise individuals at the forefront of moral progress. These examples demonstrate the core role that personality psychology is playing in the study of prosocial and moral behaviour, as well as the critical mass emerging in the Australian context around these themes.